Den danske Sprogteknologiske Ordbase og dens anvendelse i værktøj til leksikografiske formål - Braasch, Anna (Nordiske Studier i Leksikografi, 2006)
The Danish Lexicon for Language Technology Applications (STO) and its use in a tool for lexicographic purposes. This article deals with the largest and most comprehensive computational lexicon for Danish. Firstly, the development principles, the lexical coverage and the linguistic content of this lexicon are presented. This part focuses on the treatment of inflectional morphology by means of the Remove/Add computing method. Secondly, the development and functionalities of a flexible and effective lemmatiser program for Danish are discussed; the rules of the lemmatiser have been derived from the STO morphology data. A few examples illustrate the use of the lemmatiser in solving lexicographic tasks. Finally, the user-interface for online look-ups in the STO database is described: it transforms the computational lexicon into an electronic dictionary making it a useful source of lexical knowledge for lexicographers and other interested users. Also a number of useful web addresses, viz. to the STO database, the lemmatiser and relevant documentation, also in English, are provided.